Does Late-Onset Huntington Disease Represent a Distinct Symptomatic Picture? Evidence for a Selective Deficit in Executive Function and Emotion Recognition, in the Absence of Behavioral and Psychiatric Disorders - Cossu, Maria Cristina; Conti, Matilde; Palma, Veronica Di; Boccia, Maddalena; Sabatini, Umberto; Guariglia, Cecilia (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
Huntington Disease (HD) is an autosomal-dominant, neurodegenerative disorder, including motor, cognitive, emotional and behavioral symptoms. Motor symptoms used to set the clinical onset, typically emerge in the middle age. Here, we describe the case of a patient, who received a genetic diagnosis at 75 years and developed motor symptoms at 80. The Patient shows severe motor symptoms in the absence of personality changes or psychiatric disorders typically observed in HD. For what attain neuropsychological profile, it results unaltered apart from a specific deficit in emotion recognition and general slowness on executive functioning tasks, reflecting a specific trade-off between accuracy and rate of performances, that is a selective impairment in fine-tuning of resources. Both of these deficits in the Patient could be ascribable to the frontostriatal atrophy, evidenced by Computed Tomography. While deficit in emotion recognition is a well-known symptom in HD, a deficit in fine-tuning of resources regards a specific aspect of executive function. The ability of fine-tuning resources is the latest step in the development of executive functions, and it could be also the first level to be impaired in HD. We proposed that deficit in fine-tuning of resources could be the core of the neuropsychological deficit in late-onset HD.